The Art of Inegrative Counseling / 3rd Edition - Corey Gerald (Brooks/Cole Publishing Company, 2009)
This Textbook is the result of an innovative and collaborative global development process designed to engage students and deliver content and cases with global relevance. Beginning of Counseling, The Therapeutic Relationship, Establishing Therapeutic Goals, Understanding and Addressing Diversity, Understanding and Working With Resistance, Cognitive Focus in Counseling, Emotive Focus in Counselling, Behavioral Focus in Counseling, An Integrative Perspective, Working with Transference and Countertransference, Understanding How the Past Influences the Present and the Future, Working Toward Decisions and Behavior Change, Evaluation and Termination.